Iran Looking East An Alternative to the EU? - Annalisa Perteghella (Pubblicazioni ISPI, 2020)
In February 2018, anticipating the US withdrawal from the JCPOA, Iran's Supreme Leader Ayatollah Ali Khamenei declared a policy of "preferring East over West", thus paving the way for deeper cooperation with Asian powers such as China, Russia, and India. Differently from the "Look East" policy promoted during the presidency of Ahmadinejad (2005-2013), the current Iranian strategy is not only functional to escape the US-led isolation, but it rather seems devoted to the consolidation of a block of power which can commit to security and economic schemes in alternative to the Western-dominated ones. This ISPI report aims to answer few crucial questions: Which are the major initiatives promoted within Iran's "Look East 2.0" strategy? To what extent will Tehran succeed in creating a solid Eastern block? What will be the influence of the wider geopolitical context? And finally, what role is left for the EU?